2020
DOI: 10.3389/fendo.2020.00517
|View full text |Cite
|
Sign up to set email alerts
|

Computational Approaches for the Discovery of GPER Targeting Compounds

Abstract: Estrogens exert a panel of biological activities mainly through the estrogen receptors α and β, which belong to the nuclear receptor superfamily. Diverse studies have shown that the G protein-coupled estrogen receptor 1 (GPER, previously known as GPR30) also mediates the multifaceted effects of estrogens in numerous pathophysiological events, including neurodegenerative, immune, metabolic, and cardiovascular disorders and the progression of different types of cancer. In particular, GPER is implicated in hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…Other molecules having an agonist/antagonist action towards ERs are known to bind GPER, like, for instance, tamoxifen [ 43 ], raloxifene [ 44 ], bisphenol A [ 45 ], and also plant derived flavonoids, such as genistein [ 46 , 47 ], quercetin [ 48 ], and resveratrol [ 49 ]. There is, notably, an important structural heterogeneity among molecules that are able to target GPER, clearly hampering the prediction and identification of new ligands [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other molecules having an agonist/antagonist action towards ERs are known to bind GPER, like, for instance, tamoxifen [ 43 ], raloxifene [ 44 ], bisphenol A [ 45 ], and also plant derived flavonoids, such as genistein [ 46 , 47 ], quercetin [ 48 ], and resveratrol [ 49 ]. There is, notably, an important structural heterogeneity among molecules that are able to target GPER, clearly hampering the prediction and identification of new ligands [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the highest binding energies for E2 and G1 were detected in the human GPCR-based model (6LFL), suggesting that this is the most realistic model. In this regard, Grande et al ( 64 ) reported that the interaction of G1 and E2 with GPER occurs in an intracellular region. However, a molecular docking for deciphering the GPER agonist interactions reported that a ligand could be recognized at different binding sites depending on the used structural GPER conformation ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…It works in concert with ERα and its alternative spliced isoform ERα36, as well as with the growth factor receptors EGFR and IGF-1R 30 32 . As strongly suggested by staining and docking studies, the pharmacological effects of ERα17p result from its binding within the ligand-binding site of GPER (Kd in the micromolar range) 23 , 33 . Remarkably, ERα17p induces at low doses and in short times (1.5 mg/kg body weight, three times a week for four weeks) a decrease of about 50% of the size of xenografted triple negative breast tumors, in mice 21 .…”
Section: Introductionmentioning
confidence: 95%